2014
DOI: 10.1371/journal.pone.0097718
|View full text |Cite
|
Sign up to set email alerts
|

Temperate Mountain Forest Biodiversity under Climate Change: Compensating Negative Effects by Increasing Structural Complexity

Abstract: Species adapted to cold-climatic mountain environments are expected to face a high risk of range contractions, if not local extinctions under climate change. Yet, the populations of many endothermic species may not be primarily affected by physiological constraints, but indirectly by climate-induced changes of habitat characteristics. In mountain forests, where vertebrate species largely depend on vegetation composition and structure, deteriorating habitat suitability may thus be mitigated or even compensated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 61 publications
5
66
0
1
Order By: Relevance
“…Gap characteristics such as number, density, size, spatial coverage and form have been confirmed as valuable predictors in various habitat models: Zellweger et al [6] and Braunisch et al [15] used the density (number of gaps per ha) to model the effect of forest structural complexity on multi species occurrence of four temperate mountain forest bird species: Capercaillie, Hazel Grouse (Bonasa bonasia), Three-toed Woodpecker (Picoides tridactylus) and Pygmy Owl (Glaucidium passerinum). Derived metrics describing the geometry of gap have been used for example by Braunisch and Suchant [71] to define an optimal proportion of gap area for the Capercaillie-friendly habitats, or by Getzin et al [28] who used a perimeter-to-area ratio and gap shape complexity index to assess floristic diversity of the forest understory.…”
Section: Application In Biodiversity Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Gap characteristics such as number, density, size, spatial coverage and form have been confirmed as valuable predictors in various habitat models: Zellweger et al [6] and Braunisch et al [15] used the density (number of gaps per ha) to model the effect of forest structural complexity on multi species occurrence of four temperate mountain forest bird species: Capercaillie, Hazel Grouse (Bonasa bonasia), Three-toed Woodpecker (Picoides tridactylus) and Pygmy Owl (Glaucidium passerinum). Derived metrics describing the geometry of gap have been used for example by Braunisch and Suchant [71] to define an optimal proportion of gap area for the Capercaillie-friendly habitats, or by Getzin et al [28] who used a perimeter-to-area ratio and gap shape complexity index to assess floristic diversity of the forest understory.…”
Section: Application In Biodiversity Studiesmentioning
confidence: 99%
“…Getzin et al [28] showed that very high-resolution images from unmanned aerial vehicles (UAV) can be used to effectively assess forest gaps and associated plant biodiversity in temperate forests. In recent years many studies confirmed the benefit from including forest structure parameters such as canopy cover and forest gaps derived from LiDAR into habitat models showing LiDAR to deliver precise, reproducible and high resolution information for answering a variety of ecological questions [5,6,15,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these changes can affect bird abundances and bird community composition. Climate change affects not only composition and configuration of forests (Bolte and Degen 2010) but also forest structure and the relative performance of tree species (Hanewinkel et al 2013), which may on the one hand amplify negative climate-related impacts on species' habitats but also offers additional potential for mitigation (Braunisch et al 2014). …”
Section: Scenarios On Forest Conversionmentioning
confidence: 99%
“…Generally, the reliable prediction of ecological and biogeographic responses to climate change and future climate-driven land-use changes poses a serious challenge for ecologists (Jackson et al 2009). Intensive research has been conducted on projecting climate-driven changes of species distributions, but few studies have attempted to include both climate and land-use variables for predicting species distribution change (Jetz et al 2007;Braunisch et al 2014). Typically, spatial studies on the impact of climate change have focused on the prediction of range contractions and range shifts but not on the changes of population size.…”
Section: Introductionmentioning
confidence: 99%